2012
DOI: 10.1007/s00396-012-2610-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of gas delay time on the hierarchical crystalline structure and mechanical property of HDPE molded by gas-assisted injection molding

Abstract: The relationship among the processing parameters, crystalline morphology, and macroscopic properties in injected molded bar becomes very complicated due to existence of temperature gradient and shear gradient along the sample thickness. To enhance the shear strength, gasassisted injection molding (GAIM) was utilized in producing the molded bars. The aim of our research was to explore the relationship between processing conditions and the spatial variation of the hierarchy structure as well as the mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Both the ITD and the STD in Case D are higher than those in Case C, and the cooling rate of Case D is thus higher than that of Case C. When the dimensionless cooling time ( τ ) reaches 1.0, the cooling rate ranks as A > B > D > C ( Figure 1D), which is consistent with the consequence of STD. From the comparison among Figures 1A -1D, it was concluded that the cooling rate of Case D is higher than that of Case C, wherein Case D has higher ITD than Case C. Although Cases A and B have the same ITD, the cooling rate of Case A is obviously higher than Case B as Case A has a lower T w , indicating that the mold temperature exerts more significant influence on the control of the cooling rate in the plastic IM process [35,42] . It was found that the cooling rate is closely related to the thermal gradient field with phase change [39] .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Both the ITD and the STD in Case D are higher than those in Case C, and the cooling rate of Case D is thus higher than that of Case C. When the dimensionless cooling time ( τ ) reaches 1.0, the cooling rate ranks as A > B > D > C ( Figure 1D), which is consistent with the consequence of STD. From the comparison among Figures 1A -1D, it was concluded that the cooling rate of Case D is higher than that of Case C, wherein Case D has higher ITD than Case C. Although Cases A and B have the same ITD, the cooling rate of Case A is obviously higher than Case B as Case A has a lower T w , indicating that the mold temperature exerts more significant influence on the control of the cooling rate in the plastic IM process [35,42] . It was found that the cooling rate is closely related to the thermal gradient field with phase change [39] .…”
Section: Resultsmentioning
confidence: 96%
“…In our recent studies [17, 35 -39] , the cooling stage of IM was numerically investigated using the enthalpy transformation methodology (ETM) [10,40] , which is a useful way to handle the multidimensional phase-change issues [39,41] . Our findings suggested that the mold temperature exerts more significant influence on the cooling rate compared with the melt temperature [35,42] .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…After being pelletized, the pellets were molded by both a gas-assisted injection molding (GIAM) and common injection molding (CIM) processing. For GAIM processing, its main feature is to impose to a strong shear field on the polymer melt, and provide a fast cooling rate of polymer, which immensely increase the relaxation time of polymer chains [24]. The temperature profiles of the injection molding machine were 170,190,190, and 190 C from hopper to nozzle.…”
Section: Preparation Of Pc Microfibrills and Samplesmentioning
confidence: 99%
“…In previous work, we presented the spatial variation of hierarchy structures and mechanical properties of HDPE samples produced via GAIM under different gas pressures and gas delay times . In order to systematically investigate the relationship between processing conditions and flow‐induced microstructure in GAIM as a long‐term project, research on HDPE with series of melt temperature is one of the necessary subjects.…”
Section: Introductionmentioning
confidence: 99%